Functional Outcome of Epidural Steroid Injection in the Treatment of Chronic Low Backache due to Intervertebral Disc Prolapse - R Sahaya Jose; SL Binesh; N Kattu Bava; M Syed Moosa (Journal of Orthopedics and Joint Surgery)
Introduction: In the Indian population, chronic low back pain is becoming quite frequent, with prolapsed intervertebral discs being one of the most common causes. Low back pain may result from compression as well as mechanical irritation brought on by the release of proinflammatory mediators brought on by disc degeneration and herniation. One of the most popular conservative treatments for lumbar prolapsed intervertebral discs is epidural steroid injections (ESIs). Aims and objectives: The aim of the present study was to determine the functional outcome of ESI in treatment of chronic low backache due to intervertebral disc prolapse (IVDP) using Oswestry Disability Index (ODI) and numeric pain rating scale (NPRS) scoring system at baseline, 1 month, 3 months, 6 months, and 1 year. Materials and methods: Prospective study in which patients of age from 20 years with chronic low backache attending orthopedics outpatients and inpatients in tertiary care center were included. The process was explained to each patient. Every patient provided written and informed consent. At baseline, a neurological and spinal examination was performed. There are two ways to categorize ESIs: the needle path (transforaminal and interlaminar) and the site (lumbar, thoracic, or cervical). At baseline, 1 month, 3 months, 6 months, and 1 year, patients are evaluated using objective standards like the straight leg raise (SLR) and subjective measures like pain and impairment as determined by the ODI and NPRS. Numbers, percentages, means, and standard deviations were used to express the data. Version 20.0 of SPSS was employed for the analysis. The Chi-squared test will be used to determine the statistical significance of the relationship between the functional outcome of an ESI and qualitative indicators. A statistically significant value was defined as a p-value of <0.05. Results: IVDP occurred most frequently at the L4–L5 level, affecting 16 patients (45.71%). Of the patients in the study, more suffered from radiating pain to the left than the right (18 patients, or 51.43%), and 17 patients, or 48.57%, reported doing so. The mean pre-ODI score was 68.91 with a standard deviation of 4.58. Subsequent to the ESI, the ODI score demonstrated a downward trend (p < 0.05). The mean pre-NPRS score was 8.20 with a standard deviation of 2.87. Subsequent to ESI, the NPRS decreased to an average of 3.14 ± 2.85 (p < 0.05). The pre-SLR value was 61.74 ± 1.48, while the post-SLR value after 1 year of follow-up was 73.42 ± 13.36 (p = 0.03). Conclusion: ESI proved to be an effective management strategy for patients experiencing chronic low back pain resulting from a lumbar prolapsed intervertebral disc.